Transforming Sociology Learning Methods with Smartboards - Taufiq Aziz; Nadia Hartatik; Putri Dwi Permata Indah (LPPM Undiksha, 2025)
This study examines changes in Sociology teaching methods through the integration of smartboard technology and explores teachers’ and students’ perceptions of the use of digital media in the learning process. The research adopts a qualitative approach with a case study design grounded in symbolic interactionism theory. Data were collected through participant observation and in-depth interviews involving three teachers and twelve senior high school students who had implemented smartboards in Sociology instruction. The findings reveal that the use of smartboards enhances student participation, facilitates the understanding of abstract sociological concepts, and fosters a more interactive learning environment. Teachers reported that this digital medium enriches instructional strategies and supports the linkage between sociological theories and relevant social dynamics. Identified challenges include limited technological infrastructure, technical disruptions, and insufficient teacher training. The study concludes that digital transformation in learning not only improves the quality of the instructional process but also reshapes relational patterns among teachers, students, and learning materials. Recommendations emphasize the need for equitable access to technological facilities, strengthened professional development for teachers, and the systematic integration of interactive media into the development of the Sociology curriculum.